An Odontologist’s Key to Sex Determination: Study Analysis of Mandibular Canine Teeth in South Indian Population - Grover, Maneel; Bai, R Girija; Ram, Tharaka; Puri, Pooja Malik; Ghodke, Kanchana R (Journal of Orofacial Research, 2013)
Sex determination of a person becomes the first priority of a forensic investigator in the process of identification. Dental evidence pours in an invaluable informative data towardachieving the final positive results in establishing the unknown’s identity. Studies have shown that the mandibular canine resist disease, survive extreme postmortem environmental conditions and presents the highest sexual dimorphism amongst all teeth, making them an ideal teeth in forensic identification procedures. The aim of present study was to know the use of the mandibular Canine teeth’s morphological measurements in assessing sex in South Karnataka population. In the sample size of 80 males and females (40 males and 40 females) in the age-group 18 to 22 years, mandibular canine width and intercanine distance measurements were noted intraorally. The MCI and sexual dimorphism was calculated.